Stabilized FEM for Convection-Diffusion Problems on Layer-Adapted Meshes (Journal of Computational Mathematics, 2018)
The application of a standard Galerkin finite element method for convection-diffusionproblems leads to oscillations in the discrete solution, therefore stabilization seems to benecessary. We discuss several recent stabilization methods, especially its combination witha Galerkin method on layer-adapted meshes. Supercloseness results obtained allow animprovement of the discrete solution using recovery techniques.